PENERAPAN GOOD GOVERNANCE BERBASIS BIROKRASI PEMERINTAHAN DIGITAL UNTUK MENGATASI PANDEMI COVID-19 DI INDONESIA - Septony B. Siahaan; Arthur Simanjuntak; Wesly A. Simanjuntak; Dompak Pasaribu (Universitas Methodist Indonesia, 2022)
Since 2019, many countries in the world have faced health, economic, social and political shocks and difficult challenges to deal with the COVID-19 pandemic, including Indonesia. With these conditions, the performance of the government system in dealing with the pandemic is tested transparently in public. However, the implementation of good governance by the Indonesian government itself is carried out with steps and decisions that will be taken and implemented through the government bureaucracy digitally to the community in order to reduce the positive number of COVID-19. The implementation of good governance also needs to be supported by other important elements that are improved by the digital governance bureaucracy, namely transparency, accountability, efficiency and effectiveness.